Cálculo do custo do capital de terceiros: uma análise comparativa entre as formas de cálculo das empresas do novo mercado no período de 2008 a 2012 - Vicario Junior, Ezio (2013)
The main objective of this study is evaluate the differences between two methodologies used to calculate the cost of third part capital, especially after Brazilian Law 11.638/2007 and 11.941/2009 and guidelines issued by Accounting Pronouncements Committee that brought significant changes in the financial statements. The first calculation method uses the information available in the year's Balance Sheet and Income Statement and, the methodology, the data contained in the Financial Statements notes. The study scope selected 38 companies listed on the "Novo Mercado" of Bovespa's Corporate Governance, from 2008 to 2013, companies that use to provide to the market and stakeholders transparency, high quality information and the necessary level of disclosure required for a business decision. Considering this universe of 38 analyzed companies, it is possible to note that there are significant differences between the two methodologies, s howing conflict of information and, therefore do not meet the expectations of stakeholders. The analyze also showed that the data included in the Financial Statement Explanation also need a standardization, which would make the analysis and comparisons between companies easier